The Influence of Content Marketing, Delivery Services, and Product Variety on Purchase Decisions at Yan Farm Sheep Farm - lustono, Lustono; Adi, Muhammad Aldiansyah; Maesaroh, Siti; Suryani, Ratna (STIE Pelita Nusantara Semarang, 2026)
This study aims to analyze the influence of content marketing, delivery orders, and product variation on consumer purchase decisions at Yan Farm Sheep Farm. The development of technology and the increasing digital activities provide opportunities for livestock business actors to market their products more effectively. Attractive content marketing, an efficient ordering system, and product diversity are important factors in attracting consumer interest. The research method used is quantitative with a descriptive and associative approach. Data is obtained through the distribution of questionnaires to respondents who are consumers of Yan Farm Sheep Farm. The analysis technique used is multiple linear regression analysis to examine the influence of each independent variable on the dependent variable. Research results show that content marketing, delivery order, and product variations both partially and simultaneously have a significant effect on purchasing decisions. Among the three variables, content marketing has the most dominant influence. These findings provide important implications for the marketing strategy of Yan Farm Sheep Farming to focus more on improving the quality of digital content and ordering services.